Ultrasound diaphragmatic excursion during non-invasive ventilation in ICU: a prospective observational study - Barbariol, Federico; Deana, Cristian; Guadagnin, Giovanni Maria; Cammarota, Gianmaria; Vetrugno, Luigi; Bassi, Flavio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Diaphragmatic dysfunction is seen in up to 60% of critically ill patients with respiratory failure, and it is associated with worse outcomes. The functionality of the diaphragm can be studied with simple and codified bedside ultrasound evaluation. Diaphragm excursion is one of the most studied parameters.The aim of this study was to assess the prevalence of diaphragmatic dysfunction in critically ill non-intubated patients admitted to a general intensive care unit with acute respiratory failure.Methods: We collected data, including ultrasound diaphragm excursion, at 2 time points: at T0 (at the time of recruitment, just before starting NIV) and at T1 (after one hour of NIV).Results: A total of 47 patients were enrolled. The prevalence of diaphragm dysfunction was 42.5% (95% CI 28, 3 - 57,8). Surgical patients showed a higher incidence (relative risk of 1.97) than medical patients. Mean DE was not significantly different between NIV responders (1,35 ± 0.78 cm) and non-responders (1.21 ± 0.85 cm, p 0,6). Patients with diaphragmatic dysfunction responded positively to NIV in 60% (95% CI 36.0 - 80.9%) of cases, while patients without diaphragmatic dysfunction responded positively to the NIV trial in 70.4% (95% CI 49.8 - 86.2%) of cases (p = 0.54). Taking the use of ultrasound diaphragm excursion as a potential predictor of NIV response, the corresponding ROC curve had an area under the curve of 0.53; the best balance between sensitivity (58.1%) and specificity (62.5%) was obtained with a cut-off diaphragm excursion of 1.37 cm.Conclusions: Diaphragm dysfunction is particularly frequent in critically ill patients with respiratory failure. The functionality of the diaphragm can be effectively and easily tested by bedside ultrasound examination. Overall, our results point towards tentative evidence of a trend of a different response to NIV in patients with vs without diaphragmatic dysfunction.